Symptoms and adverse events in controlled human infection models - Götz, Karen; Luga, Poleta; Rengel, Jörg; Masur, Mei; Juárez-Hernández, Marcela; Bekeredjian-Ding, Isabelle (Frontiers in Medicine, 2025)
The potential and positioning of controlled human infection models (CHIMs) and human challenge trials (HCTs) in the investigation of infectious pathogens and efficacy of new anti-infectives or vaccines are under evaluation. CHIMs and HCTs can provide supporting data for decision-making in the development of new medicines (“fast failure”). However, it is important to consider that, like in any phase 1 trial, CHIM volunteers have no direct health benefit. Approval by an ethics or regulatory board implies cautious evaluation of risk and potential safety issues. In this study, we chose a syndromic approach to summarize CHIM and HCT adverse events (AEs). AEs were grouped by disease entities, e.g., enteric, respiratory, vector-borne, and parasitic infections. The analysis concludes that severe AEs are rare. It confirms that AEs reflect symptoms of CHIM infections and are less prevalent in CHIM intended for the induction of carriage. Furthermore, the number of subjects affected reflects the attack rate and individual predisposition. Rarely, AEs affect the study participants’ daily activities, ranging from impairing and preventing routine tasks to requiring emergency room visits or hospitalizations. Nevertheless, while AEs guide ethical and regulatory considerations, symptoms are needed as endpoints for evaluation of the efficacy of drugs or vaccines. Finally, we observe a lack of harmonization in the reporting and grading of AEs. This reveals an eminent need for a reporting structure that allows accessibility and comparability of data sets.